Laparoscopic Renal Cryoablation - Schiffman, Marc; Moshfegh, Amiel; Talenfeld, Adam; Del Pizzo, Joseph J. (Seminars in Interventional Radiology, 2014)
In light of evidence linking radical nephrectomy and consequent suboptimal renal function to adverse cardiovascular events and increased mortality, research into nephron-sparing techniques for renal masses widely expanded in the past two decades. The American Urological Association (AUA) guidelines now explicitly list partial nephrectomy as the standard of care for the management of T1a renal tumors. Because of the increasing utilization of cross-sectional imaging, up to 70% of newly detected renal masses are stage T1a, making them more amenable to minimally invasive nephron-sparing therapies including laparoscopic and robotic partial nephrectomy and ablative therapies. Cryosurgery has emerged as a leading option for renal ablation, and compared with surgical techniques it offers benefits in preserving renal function with fewer complications, shorter hospitalization times, and allows for quicker convalescence. A mature dataset exists at this time, with intermediate and long-term follow-up data available. Cryosurgical recommendations as a first-line therapy are made at this time in limited populations, including elderly patients, patients with multiple comorbidities, and those with a solitary kidney. As more data emerge on oncologic efficacy, and technical experience and the technology continue to improve, the application of this modality will likely be extended in future treatment guidelines.
Keywords: renal masses; cryoablation; cryosurgery; laparoscopic cryoablation